REPRESENT: REPresentativeness of RESearch data obtained through the ‘General Informed ConsENT’ - Cristina Bosmani; Sonia Carboni; Caroline Samer; Christian Lovis; Thomas Perneger; Angela Huttner; Bernard Hirschel (BMC Medical Ethics, 2023)
Abstract Background We assessed potential consent bias in a cohort of > 40,000 adult patients asked by mail after hospitalization to consent to the use of past, present and future clinical and biological data in an ongoing ‘general consent’ program at a large tertiary hospital in Switzerland. Methods In this retrospective cohort study, all adult patients hospitalized between April 2019 and March 2020 were invited to participate to the general consent program. Demographic and clinical characteristics were extracted from patients’ electronic health records (EHR). Data of those who provided written consent (signatories) and non-responders were compared and analyzed with R studio. Results Of 44,819 patients approached, 10,299 (23%) signed the form. Signatories were older (median age 54 [IQR 38–72] vs. 44 years [IQR 32–60], p < .0001), more comorbid (2614/10,299 [25.4%] vs. 4912/28,676 [17.1%] with Charlson comorbidity index ≤ 4, p < .0001), and more often of Swiss nationality (6592/10,299 [64%] vs. 13,813/28,676 [48.2%], p < .0001). Conclusions Our results suggest that actively seeking consent creates a bias and compromises the external validity of data obtained via ‘general consent’ programs. Other options, such as opt-out consent procedures, should be further assessed.